THE ROLE OF THE TEACHER IN CHARACTER FORMATION OF GRADE XI STUDENTS OF GKPI PRIVATE HIGH SCHOOL PADANG BULAN MEDAN Academic Year 2022/2023 - Amraz Sigh (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
This study aims to determine the Role of the PAK Teacher in Shaping the Character of Class XI Students of GKPI Padang Bulan Private High School Medan T.A 2022/2023 This type of research is a correlational descriptive. The population in this study is all of class XI SMA GKPI Padang Bulan Medan as many as 30 people because the population is small, namely only 30 people, so the entire population becomes the research sample, namely as many as 30 people with the sampling technique. The data collection instrument for variable X is a questionnaire which consists of 20 items. With the 4 aptions that were previously tested to determine validity and reliability while the instrument variable Y Documentation was in the form of a list of student scores (DKN) in schools. The results of the normality test analysis requirements of the PAK teacher's role data are normally distributed with the calculation results obtained X2count < X2table (22.33 <43.77) and PAK learning outcomes are normally distributed with the calculation results obtained X2count < X2table (18.85 <43.77) . The results of the data linearity test of the role of PAK teachers in forming character are linear with the equation Y = 22.77 + 1.22x which is linear. The results of the correlation test obtained rcount of 0.453 consulted with the price of criticism r at a significant level of 5% with a total of 30 respondents obtained rtable of 0.361, because rcount > rtable (0.453 > 0.361) this shows that there is an influence of the role of PAK teachers in the formation of class student character XI GKPI Padang Bulan Medan private high school T.A 2022/2023. Furthermore, to test the significant correlation is done using the statistical test formula (t test) to obtain a tcount of 3.41. This price is then consulted with ttable at a significant level of 95% of 1.69, because tcount > tthickness (3.41.169 α=0.05 with dk = n-2 (30-2=28) obtained a ttable of 1.69 because tcount > t table (3.41> 1.69) this shows that there is a significant influence of the role of the PAK teacher in the Formation of the Character of Class XI Students of the GKPI Padang Bulan Medan private high school T.A 2022/2023. Thus the research hypothesis is accepted as true.